Pelaksanaan Pembelajaran Anak Berkebutuhan Khusus di SLB Berasrama - Khusna, Mufida; Harsiwi, Nova Estu (STAI Nurul Islam Mojokerto, 2023)
The purpose of this study was to determine the implementation of learning for children with special needs in boarding schools. This research uses a qualitative approach with a descriptive method. Data collection techniques used include interviews, observations, and documentation studies. The analysis technique used is qualitative data analysis. The subjects in this study were elementary school teachers with Samudra Terra Athena dormitory and children with special needs with autistic types totaling 5 children and intellectual disabilities totaling 5 children. The results showed that the application of learning for children with special needs in the Samudra Terra Athena boarding school was quite good because there was continuity between activities at school and in the dormitory, in addition to the learning system has also been adjusted to the type of impairment and the child's ability. Learning activities are supported by a beautiful, clean, and cool environment. Moreover, there is a reciprocal relationship between teachers and parents. However, of course, in this application, it is undeniable that various kinds of challenges and obstacles arise both from students, teachers, and parents. This requires teachers to be responsive and careful in handling it.